Nursing Interventions Designed to Improve Healthcare in General Healthcare Settings for Adults Living with Mental Illness: A Scoping Review. (3rd October 2022) - Lafontaine, Sarah; Rassy, Jessica; Duval-Martin, Annie-Laurence; Girard, Ariane; Marceau, Mélanie; Gallagher, Frances; Hébert, Maude; Jacques, Marie-Claude
Abstract: People living with mental illness have difficulty obtaining quality physical care services. Nurses find it hard to fully assume their role and adopt a person-centered approach when they care for people with both physical and mental health problems. A scoping review was carried out to document the breadth and depth of literature on nurse interventions designed to improve nursing care in general healthcare settings for adults living with mental illness. Two researchers independently screened titles, abstracts and full documents to obtain publications, and the relevant data was extracted from individual studies. Of the 384 studies identified, 16 documents were included in the study. Few interventions have been the subject of scientific publications and they are scattered in their objectives and very heterogeneous in their content. Interventions are often included in a large program that may be difficult to apply in various care settings. There are many different nursing roles and activities in care-management and in support of behavioral changes although their main measured outcomes differ. This study highlights a tendency for interventions to relegate people with mental health problems to specialized services, which reinforces the dichotomization of services and does not favor a holistic and person-centered approach. There is an urgent need to develop and evaluate nursing interventions in general healthcare settings for adults living with mental illness. The development of relevant continuing education and training must take into account both the point of view of the people living with mental illness and that of nurses.